Growth, age and natural mortality of Notothenia rossii rossii in the Kerguelen Islands area ... - Tankevich, P. B. (Cybium, 1990)
Dynamics of age-length structure of the Kerguelen Islands population of Notothenia rossii is presented on the basis of data available for the 1970-1984 period. Growth rate, calculated by scales reading for the beginning of exploitation and later, when the structure of fish population has changed as a result of exploitation, is similar in values when compared. Quantitative estimates of growth parameters were obtained using von Bertalanffy’s equations and agree, in general, with data of other authors. Natural mortality coefficient for the Kerguelen population of Notothenia rossii was determined applying three independent methods. ...